MiR-17 overexpression in cystic fibrosis airway epithelial cells decreases interleukin-8 production - Oglesby, Irene K.; Vencken, Sebastian F.; Agrawal, Raman; Gaughan, Kevin; Molloy, Kevin; Higgins, Gerard; McNally, Paul; McElvaney, Noel G.; Mall, Marcus A.; Greene, Catherine M. (The European respiratory journal, 2015)
Interleukin (IL)-8 levels are higher than normal in cystic fibrosis (CF) airways, causing neutrophil infiltration and non-resolving inflammation. Overexpression of microRNAs that target IL-8 expression in airway epithelial cells may represent a therapeutic strategy for cystic fibrosis. - IL-8 protein and mRNA were measured in cystic fibrosis and non-cystic fibrosis bronchoalveolar lavage fluid and bronchial brushings (n=20 per group). miRNAs decreased in the cystic fibrosis lung and predicted to target IL-8 mRNA were quantified in βENaC-transgenic, cystic fibrosis transmembrane conductance regulator (Cftr)-/- and wild-type mice, primary cystic fibrosis and non-cystic fibrosis bronchial epithelial cells and a range of cystic fibrosis versus non-cystic fibrosis airway epithelial cell lines or cells stimulated with lipopolysaccharide, Pseudomonas-conditioned medium or cystic fibrosis bronchoalveolar lavage fluid. The effect of miRNA overexpression on IL-8 protein production was measured. - miR-17 regulates IL-8 and its expression was decreased in adult cystic fibrosis bronchial brushings, βENaC-transgenic mice and bronchial epithelial cells chronically stimulated with Pseudomonas-conditioned medium. Overexpression of miR-17 inhibited basal and agonist-induced IL-8 protein production in F508del-CFTR homozygous CFTE29o− tracheal, CFBE41o− and/or IB3 bronchial epithelial cells. - These results implicate defective CFTR, inflammation, neutrophilia and mucus overproduction in regulation of miR-17. Modulating miR-17 expression in cystic fibrosis bronchial epithelial cells may be a novel anti-inflammatory strategy for cystic fibrosis and other chronic inflammatory airway diseases. - Tweetable abstract ERSpublications - click to tweetOverexpression of miR-17 in cystic fibrosis airway epithelial cells decreases interleukin-8 protein production http://ow.ly/MZbXB
Gesehen am 22.06.2020